The Effect of Miniature Home, Pictures, and Spatial Intelligences on Students' Understanding of Geometric Space Concepts - Dimas Bagus Dwi Setyawan; I Nyoman Sudana Degeng; Nurmida Catherine Sitompul (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2020)
This study was aimed at determining whether there was an interactive effect of media (miniature home vs. picture) and spatial intelligence on the ability to understand the concept of space. The hypothesis proposed was that there was an effect of using media (miniature home vs. pictures)and spatial intelligence on understanding the spatial concept of the first-grade elementary school students.The subjects were students from an elementary school in Surabaya totaling 66 students assigned into control and experimental classes. The study used a random assigment posttest control group experimental design. The data were collected using tests on spatial intelligence and understanding of the concept of space. The data were analyzed using ANOVA after the tests for homogeneity and normality were done, The results of this study revealed that (1) there was a significant effect of using miniature home, picture, and spatial intelligence on the students ‘understanding of spatial concepts, (2) there was a significant influence of the level of spatial intelligence on understanding the concept of space. The group of students who have high spatial intelligences get the learning outcomes of the geometric space better than the group of students who have low spatial intelligences, and (3) there is no interactive influence between learning using miniature home as the media and pictures as the media and the students' spatial intelligences on the subject of geometricspace for the first students of the elementary school.